Aqueous glycerol to glyceric acid and green hydrogen by visible-light-driven photocatalysis with Ni/Co(PO4)2-TiO2: parallel utilization of holes and electrons - Nivedhitha, Thazhath R.; Bajpai, Himanshu; Oommen, Jiffin Varghese; Abraham, Athira; Chauhan, Inderjeet; Gopinath, Chinnakonda S. (ACS Sustainable Chemistry & Engineering, 2024)
Replacing the kinetically sluggish oxygen evolution reaction (OER) with the oxidation of an abundantly available organic molecule to value-added product(s) (VAPs) at low voltage along with the hydrogen evolution reaction (HER) is a big challenge in water splitting, either by electrolysis or sunlight-driven photocatalysis. Glycerol oxidation to a VAP is kinetically fast, compared to an OER, and offers hope to enhance sunlight-driven water splitting to hydrogen by the concurrent utilization of holes and electrons. Mixed bimetal phosphates of Co and Ni (CoxNiy(PO4)(2) (CoNiP)) with different Co:Ni ratios (10:0, 7:3, 5:5, 3:7, and 0:10) were integrated with TiO2 to generate final photocatalyst composites (x wt % CoNiP with TiO2) and employed for concurrent photocatalytic HER and glycerol oxidation. Irrespective of the weight ratios of CoNiP and TiO2, any TiO2-CoNiP composite showed better photocatalytic activity for the HER and glycerol oxidation compared to virgin TiO2. The highest HER as well as selectively generated glyceric acid yield was observed to be 54 and 67 mmol/g, respectively, after 25 h of reaction under 1 sun conditions with TiO2-CoNiP-5:5. An increase in catalytic activity can be attributed to the formation of p-n heterojunctions of the constituent component along with uniform distribution of CoNiP to effectively utilize the charge carriers for redox reactions. Highly selective oxidation of glycerol to glyceric acid (85%), along with other minor products, is also demonstrated, which offers further scope to use solar light to generate VAPs in a sustainable manner. A simple comparison of H-2 yield and all oxidized products together indicates the better utilization of holes for the latter, and hence, there is scope to increase HER and possibly the whole photocatalytic activity.
Keywords: biomass component; earth-abundantmaterial; energy conversion; organicvalorisation; water splitting

Synthesis of Pd-integrated carbon Dot@TiO2 thin film for photocatalytic glycerol reforming reaction for producing hydrogen - Abraham, Athira; Salgaonkar, Kranti N.; Nivedhitha, Thazhath R.; Ekal, Vishal Ashok; Kondhekar, Deepali; Chakraborty, Shubhankar; Gopinath, Chinnakonda S.; Saha, Avishek (Chemistry-an Asian Journal, 2025)
A series of thin-film photocatalysts comprising TiO2 modified with carbon dots (CDs) dispersed either with palladium (Pd-CD/TiO2) or nickel (Ni-CD/TiO2) were synthesized via solid-state and wet-impregnation methods. Morphological characterization (HR-TEM, SEM-EDS) confirmed the anatase phase of TiO2 and the atomic dispersion of metal-integrated CDs on its surface. UV-vis DRS and XPS analyses revealed a marginal red shift in band-gap and the presence of sp2-hybridized graphitic carbon, and metal-carbon interactions, indicating enhanced light absorption and charge separation through Schottky junctions. Under direct sunlight illumination, Pd-CD/TiO2 thin film exhibited superior hydrogen yield (1167 mu mol g-1 h-1) and maintained stability over 25 h, outperforming Ni-CD/TiO2 (494 mu mol g-1 h-1) and bare TiO2 (166 mu mol g-1 h-1) photocatalyst thin films. Concurrent glycerol oxidation at neutral pH (pH similar to 7) yields glycolaldehyde (41% selectivity), formic acid, and dihydroxyacetone as value-added products. Enhanced photocurrent density and lower impedance of Pd-CD/TiO2 corroborate improved charge carrier separation and dynamics. The results demonstrate that Pd-CD synergistically improves the photocatalytic performance of the Pd-CD/TiO2 for sustainable hydrogen generation and selective biomass valorization.
Keywords: Glycerol oxidation; Graphitic carbon dots; hydrogen production; Photocatalysis; titania

Polysulfone-based polymer carbon dot membrane for optical dissolved oxygen sensing application - Kadam, Rutuja; Hattale, Gangadhar; Virole, Vishal; Pal, Sanjivani; Abraham, Athira; Paul, Aditya; Kumar, Ajay; Shevate, Rahul; Banpurkar, Arun; Kanawade, Rajesh; Saha, Avishek (Chemistry-An Asian Journal, 2026)
The precise monitoring of dissolved oxygen (DO) is essential across industrial, environmental, and biomedical applications. However, the state-of-the-art DO sensing methods often suffer from inherent limitations, which hinder their effectiveness for real-time and long-term DO monitoring. Optical DO sensing, despite its advantages, utilizes expensive metal complexes and is prone to photobleaching and slow response time. Here, we introduce a novel polymer carbon dot (PCD) as a promising candidate for lifetime-based optical DO sensing. The PCD is a metal-free, nontoxic, fluorescent, long decay-lifetime material that is synthesized through hydrothermal method. Our fluorescent PCD exhibits high emission quantum yield (24.32%), long decay-lifetime (10.43 & micro;s), and a linear response to DO concentrations ranging from 0.7 to 12.7 mg/L, with a Stern-Volmer constant of 0.1115. Further, to obtain better oxygen diffusion, high porosity, optical transparency, and high flexibility, PCD was embedded into a polysulfone matrix (PSF_PCD). The PSF_PCD membrane shows better results for the decay lifetime (9.4 & micro;s), surface energy (40.26 mN/m), and average pore diameter of 5 nm. Hence, the obtained results demonstrate the applicability of the PCD in optical DO sensors for real-time and long-term monitoring of DO levels.
Keywords: decay lifetime; dissolved oxygen; Hydrothermal method; polymer carbon dots; polysulfone-based membrane